Analisis Kinerja Algoritma C4.5 Pada Sistem Pendukung Keputusan Penentuan Jenis Pelatihan - Chaulina Alfianti Oktavia; Rahmadwati Rahmadwati; Purnomo Budi Santoso (Fakultas Teknik, Universitas Brawijaya, 2015)
Abstract - This study describes the application of the algorithm C4.5 on decision support systems to support trainees in PPTIK STIKI Malang in choosing the appropriate type of training. Decision support system based on several criteria derived from the data filled out by participants prior to register as a participant. Further analysis using an algorithm that is used to form a C4.5 decision tree. The decision tree is a method of classification and prediction that represent rules. the rule is then developed using RGFDT (Rule Generation From Decision Tree). Results of testing done by comparing the system with Weka and showed an accuracy of 90%.Keywords—Algorithm C4.5, Decision Support System, RGFDT